2018
DOI: 10.1002/jcp.26625
|View full text |Cite
|
Sign up to set email alerts
|

Yes‐associated protein mediates human embryonic stem cell‐derived cardiomyocyte proliferation: Involvement of epidermal growth factor receptor signaling

Abstract: Unlike mature cardiomyocytes, human pluripotent stem cell-derived cardiomyocytes exhibit higher proliferative capacity; however, the underlying mechanisms involved are yet to be elucidated. Here, we revealed that the Yes-associated protein (YAP) plays a critical role in regulating cell proliferation in association with epidermal growth factor receptor (EGFR) in human embryonic stem cell-derived cardiomyocytes (hESC-CMs). Our results show that low-density culture significantly promotes the proliferation of hESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Density-dependent proliferation is well documented in other cell types 10 . Indeed, a previous study has shown that human embryonic stem cell-derived cardiomyocytes incorporate more BrdU when plated at “low” density (~268 cells/mm 2 ) as opposed to “high” density (~3846 cells/mm 2 ) 11 . Given our observations and this previous study, we sought to quantify the relationship between plating density and proliferation in hiCM.…”
Section: Resultsmentioning
confidence: 99%
“…Density-dependent proliferation is well documented in other cell types 10 . Indeed, a previous study has shown that human embryonic stem cell-derived cardiomyocytes incorporate more BrdU when plated at “low” density (~268 cells/mm 2 ) as opposed to “high” density (~3846 cells/mm 2 ) 11 . Given our observations and this previous study, we sought to quantify the relationship between plating density and proliferation in hiCM.…”
Section: Resultsmentioning
confidence: 99%
“…We next wanted to identify an assay that could model a uniform reduction in contact inhibition across an entire population of hiCMs. A previous study used flow cytometry and Western blotting to show that embryonic stem cell-derived cardiac myocytes begin cycling when they are sparsely plated 20 . Thus, we plated hiCMs as a monolayer or plated them sparsely.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we turned to in vitro models. It has previously been shown that plating low density human embryonic stem cell-derived CMs induces them to enter the cell cycle 20 . This was shown using flow cytometry to measure the expression of three cell cycle markers: BrdU, YAP, and cyclin D1.…”
Section: Introductionmentioning
confidence: 99%
“…We next wanted to identify an assay that could model a uniform reduction in contact inhibition across an entire population of hiCMs. A previous study used flow cytometry and Western blotting to show that embryonic stem cell-derived cardiac myocytes begin cycling when they are sparsely plated (Park et al, 2018). Thus, we plated hiCMs as a monolayer or plated them sparsely.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we turned to in vitro models. It has previously been shown that plating low density human ESC-derived CMs induces them to enter the cell cycle (Park et al, 2018). This was shown using flow cytometry to measure the expression of three cell cycle markers: BrdU, YAP, and cyclin D1.…”
Section: Introductionmentioning
confidence: 99%